Mapping the SDG 4 Process: Algorithmic Literacy Among Students of the University of Sarajevo - Adilović, Emina (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
Utilizing a mixed-method approach, this research aims to evaluate algorithmic literacy among students at the University of Sarajevo - Faculty of Political Sciences and the Faculty of Philosophy (BIH), and to assess the possibilities for improving existing practices of media and information literacy (MIL) integration. The central research question investigates how current MIL educational strategies influence students' awareness and understanding of the roles algorithms play in the digital transformation of a society striving for sustainable development. Therefore, the study encompasses a descriptive method of holistic approach elements: strategic documents, MIL book edition and MOOC modules. Subsequently, a thematic analysis of ten qualitative interviews with students further explores their experiences, attitudes, and perceptions regarding information, media, and algorithms. The research results offer insights into the potential of MIL education to support algorithmic literacy and its potential contribution to sustainable development, particularly focusing on SDG 4 - Quality Education. By aligning its findings with the objectives of a universally applicable goal, this study not only addresses the context of algorithmic literacy as an integral component of quality education but also serves as a step towards advancing the interconnectedness of open education and artificial intelligence.